A left atrial appendage closure combined procedure review: Past, present, and future perspectives. (15th May 2019) - Gasperetti, Alessio; Fassini, Gaetano; Tundo, Fabrizio; Zucchetti, Martina; Dessanai, Mariantonietta; Tondo, Claudio
Abstract: Background and Objective: Atrial fibrillation (AF) represents the most common cardiac arrhythmia worldwide; it poses a great burden in terms of quality of life reduction and yearly stroke risk. Left atrial appendage closure (LAAC) is a stroke prevention strategy that has been proven a viable alternative to antithrombotic regimens in nonvalvular AF patients. LAAC can be performed as a standalone procedure or alongside a concomitant AF transcatheter ablation, in a procedure known as "Combined procedure". Aim of this study is to summarize the scientific evidence backing this combined strategy. Methods: We reviewed the whole Medline indexed combined procedure literature, to summarize all the combined procedure study data. Results: Nine published studies regarding combined procedure were found. Data, aims, and scientific rationales were reported and commented. Conclusion: LAA combined procedure appears to be a safe and effective procedure; a careful patient selection is necessary to maximize its benefit.